A study on factor that influence job performance of nurses in Hospital Sultanah Bahiyah, Alor Setar / Muhammad Firdaus Ismail and Mohamad Fauzan Mohd Zahir - Ismail, Muhammad Firdaus; Mohd Zahir, Mohamad Fauzan (2018)
Nurses' job performance always becomes research topics by the researchers. Yet, the factors that influencing the performance of nurses always vary from one and another making this topic seems to be inexhaustible topic to become research topic. Despite the various factors that affecting nurses performance, we can sum up it into two big categories such as organizational factor and nurses-self factor. The latest trends more focus research on organizational factor rather than nurses self-factor. It is common sense where satisfied nurses with their current working conditions as well as current job, the execution of task from the related nurses will be in a higher level than those who are not (Khan, 2016). Public hospitals are very important facility to the citizens and the performance of junior employees inside it will affect the overall image of the hospitals in the public image.